Census of Population, 1980 (United States): Equal Employment Opportunity Special File ([Verlag nicht ermittelbar], 1984)
The Census Bureau has created a special subset file from the 1980 Census of Population and Housing data designed to meet the needs of Equal Employment Opportunity and affirmative action planning. It contains detailed 1980 Census data dealing with occupation and educational attainment for the civilian labor force, various race groups, and the Hispanic population. The collection contains two tabulations of the United States civilian labor force: one offering detailed occupation data and the other, data on years of school completed. The occupation tabulation includes information for 514 occupation categories organized by sex and race (including Hispanic origin). The second tabulation, years of school completed, is organized by age, sex, and race (including Hispanic origin). This collection contains 51 separate files, one for each state and the District of Columbia. Each state file contains statistics for the state, each county, standard metropolitan statistical area (SMSA), and place with a population of 50,000 or more within that state. If an SMSA crosses state lines, each state file containing a part of the SMSA will have totals for the entire SMSA. The 51 files in the collection include a total of 48,168 data records. Each of the data records contains 1,098 "substantive" variables, as well as geographic identifiers. A CENSPAC-compatible database dictionary, Part 90, is also included with this collection.